MODEL PEMBELAJARAN AKUATIK SISWA PRASEKOLAH (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
This research aims at developing and producing a product of aquatic teaching model for preschool student in the age of 4-6 years old. In more specific goal, this research would hopefully raising preschool student aquatic skill, and identifying characteristic, specialty, and the limitation of learning model that is improved. This thesis is a research and a developing study. The developing product of aquatic teaching model for preschool student, 4-6 years old, was done through several stages: designing first draft of product, expert validation, experiment in small scale, revision for first level, experiment in large scale, and revision for second level (the last revision). The subject of this research is preschool students in the age 4-6 years old from the kindergarten (TK) Al Furqon Sleman, TK ABA Mardi Putra Bantul, TK PKK 80 Sanden Bantul, TK Lembaga Tama III Bantul, and TK Pembina Bantul. There are 50 students for research subject. Expert validation was done by two sport education experts and three preschool teachers. The experiment in small scale was done to ten students and the experiment in large scale was done to 50 students. The data was collected through observation by three raters. The data consists of evaluation for product quality, suggestion for product improvement, and scoring for student skill. Validity test for Data analysis technique that was used is percentage quantitative descriptive to explore psychomotor, cognitive, and affective aspect. The result of research shows that in psychomotor aspect, according to Rater 1, from 50 students, there are 52% of students involved in good category, 46% involved in intermediate category, and 2% involved in lack category. Rater 2 states that there are 40% from 50 students involved in good category, 56 % involved in intermediate category, and 4% involved in lack category. Rater 3 argues that there are 50 % from 50 students involved in good category, 48% involved in intermediate category, and only 2% involved in lack category. In the affective aspect from 50 students that were observed, according to Rater 1 there are 62% of students involved in good category, 36 % involved in intermediate category, and 2% of the rest involved in lack category. Rater 2 says that there are 50 % of 50 students involved in good category, 46% involved in intermediate category, and 4% involved in lack category. According o Rater 3 there are 60 % of 50 students involved in good category, 38% involved in intermediate category, and 2 % involved in lack category. In the cognitive aspect from 50 students, according to Rater 1 there are 70 % of students involved in good category, 28% involved in intermediate category, and 2% involved in lack category. Rater 2 says that there are 52% of 50 students involved in good category, 34 % involved in intermediate category, and 34 % involved in lack category. Rater 3 argue that there are 68% of 50 students involved in good category, 30% involved in intermediate category, and 2% involved in lack category.There for, it can be concluded that the product of the aquatic teaching model for 4-6 years old of preschool students is influencing the psychomotor, affective, and cognitive aspect of students. Based on the fact, this research proposes as a product of aquatic teaching model for 4-6 years old of preschool students, for the teacher, in the teaching for physical movement development or motoric in preschool level.